Health Informatics and Education: An Example of Multilateral e-learning Program for Post Graduate Trainees - Figuim, Bello; Djientcheu, Vincent de Paul; Nathalie, Noumsi Tchemgui; Anne, Boli; Samuel, Nko'o Amvene (Journal of Health Informatics in Africa, 2013)
Background and Purpose: Health Information is one of the major factors contributing to better management of patient, insure patient safety and improve the quality of research. Cameroon as African Countries in general who intend to fill the gap in the field of Health education and research, demonstrates through using IT tools,  improvement in the field of health education among the community of medical  lecturers and trainees.Methods: Over a period of two years (2012-2013), we conducted an observational study in the teaching hospitals and the Faculty of Medicine of the University of Yaounde 1. We analyzed e-learning program.Results: Several e-courses of post graduate training have been developed since the creation of medical and surgical subspecialties at the faculty of medicine of Yaounde in 2010. (55 post graduate courses are available on the Dudal plate form). Many lecturers of the faculty of medicine have shown positive implication to online courses and the pedagogic orientation of the faculty is currently directed to the use of IT as the main tool in the training program of medical students and post graduate trainees. A structured post graduate e-learning program has been defined with six fields: Neuroscience, Ophthalmology, Pediatrics, Obstetrics and Gynecology, General surgery and Internal Medicine. This e-learning program was supported by collaboration of African countries (Cameroon, Mali, Senegal, Madagascar) and European countries (Switzerland, France). Also, special virtual communities have been created to strengthen the training and collaboration in several fields with the contribution of Africa Build project.Conclusions: Collaborative multilateral e-learning program for post graduate trainees seems to be helpful in our setting.Keywords: e-learning, Education, Post graduate